Flood mitigation in Santa Rosa, Laguna using the concept of sponge cities case study of a recreational park in Brgy. Aplaya - Enaguas, Kevin Christian E.
The Sponge City concept is applied to various cities around the globe. The idea of this concept is to absorb, retain, and infiltrate runoff. The idea of this study is to apply the concept of Sponge City to the City of Santa Rosa, Laguna. Flood is an issue to the city of Santa Rosa, Laguna being a part of a country located in the Western portion of the Pacific Ocean, where typhoons come and go, and is part of the growth corridor of CALABARZON where urban developments are growing, changing the landscape of the city, developing rural lands into urban concrete. The study looked in previous studies on sponge cities and existing sponge developments to formulate a list of landscape solutions. Principles and frameworks were derived from these studies and applied to the context of Santa Rosa. The runoff events in the city was calculated from rainfall events with 10, 25, 50, and 100-year return. Open spaces were mapped out and used for development scenarios. Development scenarios of 25 percent, 50 percent, and 100 percent were calculated to gauge the capabilities of the open spaces in abating flood occurences. Then, a case study of creating a recreational park applied with these landscape solutions was conducted in Brgy. Aplaya in Santa Rosa. Results showed how much of the accumulated runoff can be contained by the park. Further recommendations are provided for future research in the same topic.